Holes in Sacred Umbrellas: Non-Religious Friendship Networks and Adopting an Atheistic Worldview - Katie E. Corcoran; Christopher P. Scheitle (Secularism and Nonreligion, 2025)
Berger (1967) argued that the plausibility of a religious worldview depends on the strength of the plausibility structure supporting it. We hypothesize that a weaker religious plausibility structure (or, alternatively, a stronger non-religious plausibility structure) will increase the odds of adopting an atheistic worldview. We use waves 2 and 4 of the National Study of Youth and Religion to test the relationship between non-religious and religious friendship ties and adopting an atheistic worldview in the United States. We find that a stronger non-religious plausibility structure, regardless of how it is operationalized (e.g., percent, majority, or entirety of one’s friendship network who are not religious), is significantly associated with increased odds of adopting an atheistic worldview as an emerging adult. Even having one friend who is not religious among mostly religious friends may potentially serve for some to relativize one’s religious worldview thereby increasing the odds of adopting an atheistic worldview. Still, regardless of one’s friendship network’s composition, maintaining a non-atheistic worldview is more common than adopting an atheistic worldview suggesting that worldviews may not be as fragile as some prior research has suggested.